Clinical course, neurohumoral and hemodynamic disorders in patients with stable angina pectoris on the background of community-acquired pneumonia - N. S. Mykhailovska; T. O. Kulynych; G. V. Grytsay (Zaporozhye State Medical University, 2014)
Introduction: Coronary heart disease is among the most common problems in cardiology. The magnitude of the problem of coronary heart disease is highlighted by estimates that more than 22% of cardiac deaths among women and 20% among men occur every year. The clinical course of coronary heart disease depends on traditional risk factors, coexisting nonspecific respiratory diseases, especially community acquired pneumonia. It is known that within 30 days after community-acquired pneumonia the hospitalizations rate because of exacerbation of coronary heart disease is increased. Objective: to study the clinical course, neurohumoral and hemodynamic changes in patients with coronary heart disease after community acquired pneumonia. Materials and methods: 51 patients with coronary heart disease: stable angina pectoris, 2-3 functional class (22 men and 29 women), from 52 to 78 years old. The patients were examined during the inpatient treatment. The study involved 2 separate groups of patients with coronary heart disease. One group included 31 patients with coronary heart disease and community acquired pneumonia (the principal group). The control group included 20 patients without pneumonia. Within the first 3 days in hospital the levels of total cholesterol, high- and low-density lipoprotein cholesterol, triglyceride (BIOLATEST, company PLIVA-Lachema), high-sensitivity C-reactive protein (by solid-phase chemiluminescence analysis), daily monitoring of ECG («Kardiosens K»,Kharkov) and ultrasonography («SONOACE» 8000SE) were assessed. The data were processed by methods of variation statistics using application package «Statistica 11.0» by standard requirements. Results: The study showed that in the principal group dyspnea (2.8 times more, p <0.005), cardiac arrhythmia (by 33.39%, p <0.05) were observed frequently; lower levels of HDL-cholesterol by 25.28% (p <0.05), increased level of hs-CRP by 6.54-times (p <0.05) were revealed. The ECG monitoring data in the patients with pneumonia showed more frequent high grade ventricular extrasystoles (22.58% vs. 15%, p < 0.05), increased total duration of tachycardia episodes (204.17 ± 28.26 min. vs. 11.67 ± 9.04 min., p<0.05), silent myocardial ischemia (4.75±1.34 min vs. 3.25±1.46 min, p<0.05), depth ST-segment depression (108 ± 32.83 mV vs. 81 ± 18.11 mV, p<0,05) and significant sympathetic nervous system activation. Although there was a significant trend toward the left ventricle enlargement (EDD by 14.31% and 32.59% for the ESD, p<0,05), right ventricle enlargement (7.89%, p<0.05), reduction of left ventricular ejection fraction by 21.57% (p<0,05), VE/VA by 22.68%, increased IVRT by 24.32% and a significant pulmonary pressure increasing (by 1.62 times) as compared with patients without community acquired pneumonia (p<0,05). Correlation between C-reactive protein levels, oxygen saturation, and autonomic imbalance, the myocardial ischemia severity and structure functional indices of heart was detected. Conclusions: The clinical course of coronary heart disease in patients with community acquired pneumonia is characterized by increased prevalence of arrhythmias, duration and severity of silent myocardial ischemia, heart rate variability changes (sympathetic activation of the autonomic nervous system). The ischemic heart disease with coexisting community acquired pneumonia were associated with increased heart enlargement, decreased ejection fraction, dysfunction of left ventricle diastolic filling and mean pulmonary pressure increasing on the background of hypoxia, dyslipidemia and pro-inflammatory changes.